Fuzzy, copper-based multi-functional composite particles serving simultaneous catalytic and signal-enhancing roles. Issue 17 (19th April 2016) - Li, Xiangming; Hu, Yingmo; An, Qi; Luan, Xinglong; Zhang, Qian; Zhang, Yihe
Abstract : A facile strategy to prepare high-performance, dual-functional, catalytic and signal-enhancing copper-based composite particles is reported. Abstract : Multifunctional plasmonic particles serving simultaneously as catalysts and label-free reporting agents are highly pursued due to their great potential in enhancing reaction operational efficiencies. Copper is an abundant and economic resource, and it possesses practical applicability in industries, but no dual-functional copper-based catalytic and self-reporting particles have been reported so far. This study proposes a facile strategy to prepare high-performance dual-functional copper-based composite particles that catalyze reactions and simultaneously serve as a SERS (surface enhanced Raman spectra) active, label-free reporting agent. Polyelectrolyte-modified reduced graphene oxide particles are used as the reactive precursors in the fabrication method. Upon adding Cu(NO3 )2 solutions into the precursor dispersions, composite particles comprised by copper/copper oxide core and polyelectrolyte–graphene shell were facilely obtained under sonication. The as-prepared composite particles efficiently catalyzed the conversion of 4-nitrophenol to 4-aminophenol and simultaneously acted as the SERS-active substrate to give enhanced Raman spectra of the produced 4-aminophenol. Taking advantage of the assembling capabilities of polyelectrolyte shells, the composite particles could be further assembled onto a planar substrate to catalyze organic reactions, facilitating their application in various conditions. We expect this report to promote the fabrication and application of copper-based multifunctional particles.